Tc-99m-PSMA-SPECT/CT Is Superior to Tc-99m-MDP-SPECT/CT in the Staging of Prostatic Cancer with Osseous Metastases after External Beam Radiotherapy - Liepe, Knut; Baehr, Marcel (World Journal of Nuclear Medicine, 2022)
In the reported patient with advanced prostate cancer, a bone scan showed a false positive finding in thoracic vertebrae bone metastasis after external beam radiotherapy 2 months ago. An additional Tc-99m-prostate-specific membrane antigen scan showed a negative finding, although nonirradiated iliac bone metastasis was concordantly positive in both scans. The decrease in prostate-specific antigen-level from 156.6 ng/mL to 2.3 ng/mL indicates a strong effect of treatment, hence supporting false positivity in bone scan by flare phenomenon.
Keywords: Tc-99m-PSMA; Tc-99m-MDP; bone metastases; prostate cancer; external beam radiotherapy